Effects of cold exposure on heart clearing factor lipase and triglyceride utilization in the rat - M. Perenna Rogers (Journal of Lipid Research, 1974)
The clearing factor lipase activity of the rat heart was measured in animals kept at 4°C for several hours and was compared with that in control animals kept at 25°C. The total activity of the enzyme in the heart increased markedly on exposure to the low temperature, whether the animals were in a fed or a fasted state. The activities of both the heparin-releasable and the heparin-nonreleasable enzyme fractions were usually raised. However, only increases in the former could be correlated satisfactorily with corresponding increases in the capacity of the heart to utilize chylomicron triglyceride fatty acids perfused through it.Cold exposure also raised the plasma clearing factor lipase activity and reduced the plasma triglyceride concentration. These changes may have been due, at least in part, to the alterations in the activity of the tissue enzyme.